2012
DOI: 10.1002/eat.22069
|View full text |Cite
|
Sign up to set email alerts
|

Comparing work productivity in obesity and binge eating

Abstract: Objective: To examine productivity impairment in individuals with obesity and/or binge eating.Method: Based on current weight and eating behavior, 117,272 employees who had completed a health risk appraisal and psychosocial functioning questionnaire were classified into one of four groups. Gender-stratified analyses compared groups on four measures: absenteeism, presenteeism, total work productivity impairment, and (non-work) activity impairment.Results: Overall group differences were statistically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 14 publications
5
20
0
Order By: Relevance
“…The present results in individuals meeting DSM‐5 diagnostic criteria for BED are also consistent with previous studies that demonstrated significant impairments in work productivity and daily activity, as measured on the WPAI, in individuals who exhibit binge eating behaviour 7, 8, 20. Bedrosian et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present results in individuals meeting DSM‐5 diagnostic criteria for BED are also consistent with previous studies that demonstrated significant impairments in work productivity and daily activity, as measured on the WPAI, in individuals who exhibit binge eating behaviour 7, 8, 20. Bedrosian et al.…”
Section: Discussionsupporting
confidence: 92%
“…The WHO surveys also reported that early‐onset BED (ie, onset before completion of one's education) was associated with a reduced likelihood of being married among women and a reduced likelihood of being employed among men 5. On the Work Productivity and Activity Impairment (WPAI) scale,6 individuals who reported binge eating behaviour also reported greater impairment in work productivity and non‐work activities, as well as increased rates of absenteeism than individuals who did not report binge eating 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…Overweight in all workers and obesity in day and on-call workers were not associated with WF total and WF subscale scores. Our finding that obesity was associated with the lower WF total scores and lower WF scores for physical demands is in line with earlier studies (Neovius et al, 2009;Striegel et al, 2012;Gates et al, 2008;Mond et al, 2007;Cavuoto and Nussbaum, 2014). In particular, Gates et al showed that job limitations most affected by obesity were those with time and physical demands (Gates et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…For instance, obese individuals may be more prone to balance loss and falling than non-obese individuals during a prolonged standing task (Koepp et al, 2014 Dec 22;Mehta and Cavuoto, 2015;Peduzzi de Castro et al, 2014 Jul). Although Strigel et al did not consider specific work demands in relation to overweight and obesity, the authors reported the association between obesity and work impairment and they assessed WF by the Work Productivity Activity Impairment questionnaire (Striegel et al, 2012). In contrast, Robroek et al reported no association between obesity and productivity loss at work (Robroek et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation